2011
DOI: 10.1007/s00420-011-0657-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in subjective response to whole-body vibration under standing posture

Abstract: Our results suggest that females are subjectively more sensitive than males for fore-and-aft and lateral WBV exposure, especially at higher vibration magnitude. Therefore, the differential effects in subjective responses to WBV in females and males should be taken into account in the ISO standard currently used in discomfort evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…According to some authors, women are more sensitive to vibration and perceive their exposure as higher [33,34]; others suggested that the impact of whole-body vibration is stronger on male heart rate variability [35], and that nighttime train vibration is associated with a slightly stronger increase in the heart rate in the delayed response of men [36]. Further comparisons with our findings are hindered not only by the few occupational epidemiology studies overall but also by the different populations under investigation (i.e., white/blue-collar, men/women).…”
Section: Resultsmentioning
confidence: 99%
“…According to some authors, women are more sensitive to vibration and perceive their exposure as higher [33,34]; others suggested that the impact of whole-body vibration is stronger on male heart rate variability [35], and that nighttime train vibration is associated with a slightly stronger increase in the heart rate in the delayed response of men [36]. Further comparisons with our findings are hindered not only by the few occupational epidemiology studies overall but also by the different populations under investigation (i.e., white/blue-collar, men/women).…”
Section: Resultsmentioning
confidence: 99%
“…Cross-axis vibration measured along axes orthogonal to the vibration axis, which includes cross-talk response of the accelerometer, misalignment errors of the accelerometer, and background noise of transverse motion itself, was maintained less than 5% at all frequencies of interest (Shibata et al, 2012). Also rotational vibrations around the axes were negligible.…”
Section: Test Facilitymentioning
confidence: 99%
“…Thus the median value C j is the absolute scale value. Finally an absolute scale magnitude U i corresponding to each vibration stimulus was calculated by using the interpolation technique (Shibata et al, 2012).…”
Section: Determination Of Subjective Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Health related quality of human life and loss of independence can be also affected by natural weakening of human body and its functional systems. This leads to more frequent falls and consecutive health and mobility problems [1][2][3].…”
Section: Introductionmentioning
confidence: 99%